A subchannel based annular flow dryout model. (August 2016) - Hammouda, Najmeddine; Cheng, Zhong; Rao, Yanfei F.
Highlights: A modified annular flow dryout model for subchannel thermalhydraulic analysis. Implementation of the model in Canadian subchannel code ASSERT-PV. Assessment of the model against tube CHF experiments. Assessment of the model against CANDU-bundle CHF experiments. Abstract: This paper assesses a popular tube-based mechanistic critical heat flux model (Hewitt and Govan's annular flow model (based on the model of Whalley et al.), and modifies and implements the model for bundle geometries. It describes the results of the ASSERT subchannel code predictions using the modified model, as applied to a single tube and the 28-element, 37-element and 43-element (CANFLEX) CANDU bundles. A quantitative comparison between the model predictions and experimental data indicates good agreement for a wide range of flow conditions. The comparison has resulted in an overall average error of −0.15% and an overall root-mean-square error of 5.46% with tube data representing annular film dryout type critical heat flux, and in an overall average error of −0.9% and an overall RMS error of 9.9% with Stern Laboratories' CANDU-bundle data.